Avalia????o do papel da IL-10 nos efeitos anti-inflamat??rios do exerc??cio aer??bio na s??ndrome do desconforto respirat??rio agudo experimental - Oliveira, Nicole Cristine Rigonato de (2014)
The acute respiratory distress syndrome (ARDS) is a disease characterized by respiratory failure due to an inflammatory response, which has high morbidity and mortality. Several cytokines seem to orchestrate the acute and chronic processes, mainly mediated by toll like receptors (TLRs). The literature demonstrates that aerobic exercise (AE) is capable of decreasing the secretion of pro-inflammatory cytokines in the lungs mediated increased release of interleukin 10 (IL-10), and AE modulate expression of TLRs and antioxidant enzymes. The objective of this study was to evaluate whether the anti-inflammatory effects of AE in an experimental model of intra and extrapulmonary ARDS are mediated by IL-10. For this, the animals were subjected to physical training on a treadmill, moderate for 4 weeks. 24 hours after the last physical test, animals received LPS by intratracheally (it) (10ug / animal) or intraperitoneally (ip) (100ug / animal). After 24 hours, the animals were assessed for the number of cells and pro- and anti-inflammatory cytokines in bronchoalveolar lavage fluid (BAL) and serum were the number of neutrophils in the lung parenchyma and expression of TLR4, TLR7, SOD, ??nion and QL in lung homogenates. AE reduced accumulation of neutrophils in the lung parenchyma, so it LPS and LPS ip (p <0.01) and BAL (p <0.01). AE attenuate the levels of proinflammatory cytokines in BAL and serum (p <0.05), as measured by ELISA. AE had levels of anti-inflammatory cytokine IL-10 increased in the serum and BAL (p <0.05). AE also reduced the expression of TLR4 in lung homogenates (p <0.05) and increased the expression of TLR7 in group LPS + AE evaluated by western blotting (p <0.05). The results for the antioxidant enzyme SOD showed a significant increase in the groups submitted to AE. It follows that the impact of reduced LPS-induced ARDS, regardless of etiology, and these effects appear to be mediated by modulation of the AE secretion of anti-inflammatory cytokines, especially IL-10, modulating TLR4 and TLR7 and increased expression of SOD (p <0.05).